Relationship Between HbA1c Levels and Erythrocyte Sedimentation Rate (ESR) in Type II Diabetes Mellitus Patients at Dr. Rasidin Padang Hospital - Demitra Rona; Telambanua, Arniat Christiani (Rajaki of Tulip Medika Publisher, 2025)
Type II Diabetes Mellitus is a chronic metabolic disorder characterized by increased blood sugar due to decreased insulin secretion by pancreatic beta cells and/or impaired insulin function. The purpose of this study was to determine the relationship between HbA1c levels and the Erythrocyte Sedimentation Rate (ESR) in Type II Diabetes Mellitus patients at Dr. Rasidin Padang Regional General Hospital. This type of research employs quantitative methods and a descriptive design and was conducted in January 2024. The population was all type II diabetes mellitus patients at Dr. Rasidin Padang Regional General Hospital, totaling 55 patients, while the sampling used the total sampling technique. Data were analyzed univariately and bivariately using the Chi-square test. The results of the study showed that 40% had prediabetes HbA1c levels, and 50.9% had abnormal erythrocyte sedimentation rates (ESR). There was a relationship between HbA1c levels and erythrocyte sedimentation rates (ESR) (p = 0.015) in type II diabetes mellitus patients at Dr. Rasidin Padang Regional General Hospital. Based on the results, it can be concluded that there is a relationship between HbA1c levels and the erythrocyte sedimentation rate (ESR) in type II diabetes mellitus patients at Dr. Rasidin Padang Regional Hospital. Suggestions: All healthcare workers are expected to provide information about the relationship between HbA1c levels and the erythrocyte sedimentation rate (ESR) in patients with type 2 diabetes mellitus. Health workers should conduct HbA1c examinations more routinely in type II diabetes mellitus patients with tuberculosis